Elevational patterns of bryophyte and lichen biomass differ among substrates in the tropical montane forest of Baru Volcano, Panama. (3rd April 2019) - Rodríguez-Quiel, Eyvar E.; Mendieta-Leiva, Glenda; Bader, Maaike Y.
ABSTRACT: Introduction. Tropical montane forests support a high abundance and diversity of bryophytes and lichens on different substrates. However, quantitative information about how their biomass and water-holding capacity change with elevation is scarce. The current project assessed variation in the biomass and water-holding capacity of bryophytes and lichens on Baru Volcano, Panama. Methods. On the western slope, the bryophyte and lichen layer was collected from 600 cm 2 plots on six substrate types with four replications at eight elevations along a gradient from 1900 to 3300 m a.s.l. We recorded the thickness, water-holding capacity and biomass of all samples, as well as environmental parameters. Key results. At lower elevations substrates had a similar biomass and water-holding capacity per area, but with increasing elevation terricolous substrates showed the strongest increase (highest values at 3100 m). These patterns are associated with climatic variation along the gradient. At the highest elevations, the forest was of low stature and more light reached the forest floor. Also at these high elevations fog provides a daily wetting of the bryophytes and lichens. At lower elevations the water supply is increasingly in the form of rain, which is less frequent than the fog. Conclusions. The apparent strong coupling of biomass variations to precipitation regimes implies a high sensitivity of the bryophytes and lichens to climatic warming and changes in the cloud base elevation. Furthermore our data suggest that the importance of bryophytes and lichens for regulating ecosystem water fluxes increases with elevation, which underlines the necessity to conserve intact montane forests.